Penerapan Pembelajaran Kisah Anak dalam Al-Qur’an di Sekolah PAUD RA Arafah - Dinil Arifah; Nur Fadilah; Junita Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early childhood education (ECE) is a fundamental stage in character building. One effective method that can be used is story-based learning, especially children's stories in the Qur'an. This study aims to describe the application of children's stories in the Qur'an in PAUD institutions and identify the character values developed and their effectiveness. The approach used is descriptive qualitative with observation, interview, and documentation techniques. The results showed that the application of the story method is effective in shaping early childhood characters such as honesty, patience, and obedience. Teachers use auxiliary media such as puppets and picture books for storytelling. This research reinforces the importance of integrating Qur'anic stories in the PAUD curriculum as a medium for Islamic character education.